Progressing towards high performance non-resonant piezoelectric stepping actuators - Berry, Dipika (2023)
Piezoelectric actuators are emerging as a promising technology with their potential to deliver a system with high specific power, accuracy, quick response and resolution. Over the years, there have been significant advancements towards enhancing the working stroke through motion accumulation (stepping) mechanisms, along with the attempts to achieve higher output force, motion speed and resolution. Among these output performances, speed and force are the two key parameters which determine their potential for medium to large-scale applications. Therefore, this paper provides a comprehensive review on these two main development directions of the stepping actuators, in which the adopted design concepts are analyzed in detail. Additionally, the challenges towards the implementation of these actuators for the targeted application are highlighted along with their feasible solutions. This review aims to provide an insight into the novel design of piezoelectric actuators, geared towards extending their potential for high power applications in the future.